Functional group chemistry - Hanson, James Ralph (Wiley-Interscience, 2002)
Functional Group Chemistry presents the chemistry of functional groups with an emphasis on patterns of reactivity, the consequences of the relative electronegativity of the atoms that constitute functional groups, the role of lone pairs and the stereochemistry of reactions at a particular group. Each chapter is concluded with a series of test problems.